Predictive Factors of Pelvic Organ Prolapse and the Quality of Life Among Jordanian Women: A Case-Control Study - Qatawneh A; Qudah S; Alkouz D; Kadah A; Abu Salma B; Al-Alawneh W; Alhabosh S; Salahaldeen M; Banihamad BA; Aldmour BA; Alkouz N; Alqatawneh A; et al. (International Journal of Women's Health, 2025)
Ayman Qatawneh,1 Shrouq Qudah,2 Dania Alkouz,2 Abdulla Kadah,2 Baha’a Abu Salma,3 Waed Al-Alawneh,2 Sara Alhabosh,2 Majed Salahaldeen,2 Balqees Aref Banihamad,2 Bara’a Amer Aldmour,2 Noor Alkouz,2 Abdulrahman Alqatawneh,2 Nadia Muhaidat,1 Fida Thekrallah,1 Mohammad Abufaraj4,5 1Department of Obstetrics and Gynecology, Jordan University Hospital, The University of Jordan, Amman, Jordan; 2Faculty of Medicine, The University of Jordan, Amman, Jordan; 3Department of Food Science and Nutrition, Jerash University, Jerash, Jordan; 4Department of Special Surgery, Jordan University Hospital, The University of Jordan, Amman, Jordan; 5Department of Urology, Medical University of Vienna, Vienna, 1090, AustriaCorrespondence: Ayman Qatawneh, Department of Obstetrics and Gynecology, Jordan University Hospital, Faculty of Medicine, The University of Jordan, Amman, Jordan, Email a.qatawneh@ju.edu.joBackground: Pelvic organ prolapse (POP) is a common gynecological problem. Several risk factors have been identified to contribute to the main pathophysiological mechanism of prolapse development. However, the POP data in the Eastern Mediterranean region, including Jordan, are limited, and the risk factors associated with POP were mainly obesity and high number of vaginal deliveries. Since Jordan has a high prevalence of obesity, parity, and type 2 diabetes, the present study aimed primarily to identify the modifiable and non-modifiable factors associated with POP in Jordanian women, and secondly, to evaluate the impact of POP stages on their quality of life.Methods: This study was an age-matched case-control study conducted at the gynecology outpatient clinics at Jordan University Hospital from March 1, 2022, to December 15, 2022. The POP quantification system was used as a standardized method to identify the cases and controls. Sociodemographic, obstetrics, and gynecological characteristics were obtained and correlated with POP. Multivariable logistic regression was performed to determine the independent predictive factors of prolapse occurrence. The Prolapse Quality of Life questionnaire was employed to assess the impact of prolapse across the stages of prolapse.Results: One hundred fifty cases and 150 controls were enrolled in this study, with a median age of 44.5 years. Cystocele and rectocele were the most identified types of prolapse. Nearly 65% of women reported that they had an episiotomy during their deliveries, and 14% reported that there was a family history of prolapse. Multivariable logistic regression revealed that obesity (AOR = 2.31, 95% CI 1.07– 5.84, p = 0.03), episiotomy (AOR = 2.88, 95% CI 1.41– 5.89, p = 0.004) and family history of prolapse (AOR = 3.45, 95% CI 1.3– 9.2, p = 0.013) were associated with POP. Impairment in the quality of life was significantly higher across prolapse severity stages.Conclusion: In Jordan, obesity, episiotomy, and a family history were associated with POP. Quality of life for women with POP was notably impaired as the severity of the prolapse increased.Keywords: pelvic organ prolapse, quality of life, odds factors, Jordan